To solve this equation: 3t(t+2)=1 first rearrange:

`therefore 3t(t+2)=1` becomes `3t^2+6t-1=0`

It cannot be factored normally so use the quadratic formula:

`x=(-b+-sqrt(b^2-4ac))/(2a)` where a=3, b=6 and c=-1

`therefore x=(-6+-sqrt(36-4(3)(-1)))/(2(3))` Care with negative symbols

`therefore x=(-6+-sqrt48)/6`

`therefore x=0.1547` or `x=- 2.1547`

**Ans: x=0.1547 or x=- 2.1547**

3t(t+2)=1 first you use the distributive property 3t x everything inside the parenthesis you will end up with:

`3t^2+6t=1` then move the 1 by taking it out on both sides. you will end up with:

`3t^2+6t-1=0` the next step is to use the quadratic formula.

`-6+-sqrt(6^2-4(3)(-1))` over 6 then simplify the problem:

`-6+-sqrt(36+12)` divided by 6

`-6+-sqrt(48)` divided by 6

`(-6+-6.92)/6`

`(-6+6.92)/6` `=0.153`

`(-6-6.92)/6` `=-2.153`

x= .153 x=-2.153